2021
DOI: 10.1002/csc2.20645
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield response to cultivar and harvest time of the first crop in rice ratooning in southwestern Japan

Abstract: Rice (Oryza sativa L.) ratooning has attracted attention due to its higher yield potential compared with conventional methods. Here, field experiments were conducted in southwestern Japan in 2019 and 2020 to determine the effects of cultivar (‘Takanari’, an indica cultivar, and ‘Koshihikari’, a japonica cultivar) and harvest time of the first crop (early and late) on the grain yields of the first and second crops in rice ratooning. For Koshihikari in 2019, grain yield of the second crop did not differ between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…NIL‐ GN1A Takanari had fewer panicles of the first crop but did not have a higher NSC concentration in the stubble. Recently, we examined the relationship between grain yield of the second crop and NSC content, NSC concentration, or leaf sheath plus stem weight for Koshihikari and an indica cultivar, Takanari (Tanaka et al., 2022). In a year when Koshihikari produced a higher grain yield of the second crop than Takanari, Koshihikari tended to have a higher NSC content due to the relatively higher NSC concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NIL‐ GN1A Takanari had fewer panicles of the first crop but did not have a higher NSC concentration in the stubble. Recently, we examined the relationship between grain yield of the second crop and NSC content, NSC concentration, or leaf sheath plus stem weight for Koshihikari and an indica cultivar, Takanari (Tanaka et al., 2022). In a year when Koshihikari produced a higher grain yield of the second crop than Takanari, Koshihikari tended to have a higher NSC content due to the relatively higher NSC concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was based on a split‐plot design with the main plot as rice genotype (NIL‐ GN1A Takanari and Koshihikari) and sub‐plot as cutting height of the first crop (high and low), arranged in a randomized complete block design with three replicates. Information of air temperature and solar radiation was reported by our previous studies (Nakano et al., 2021; Tanaka et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanaka et al. (2022) also showed that low radiation capture reduced the effective panicles during the vegetative growth and the spikelets during the reproductive growth. Therefore, developing plants and cultivars with large panicles, by promoting the regenerative ability of the lower position nodes on the stubble of main‐season crops, may be crucial to the improvement of productivity in the ratoon season of WDR system.…”
Section: Discussionmentioning
confidence: 98%
“…He et al (2019) also found that the regenerative capacity was significantly positively correlated with the NSC content in the stubble of main-season crops in CLR. Higher DM accumulation in the stubble provides sufficient nutrients for the sprouting of axillary buds (Ichii & Sumi, 1983;Xu et al, 1997) and the differentiation of spikelets (Nakano et al, 2020(Nakano et al, , 2021Tanaka et al, 2022) in the ratoon season. Although the relationship between N content in the stubble of main-season crops and the regeneration capacity of ratoon season has not been reported, it is a common measure to apply N fertilizer at the 15th day after full heading of the main-season crop to promote the axillary bud sprout in the ratoon rice production (Ling et al, 1989;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%